A contractive method for computing the stationary solution of the euler equation - Moreira, Humberto Ataíde (2002)
A contractive method for computing stationary solutions of intertemporal equilibrium models is provide. The method is is implemented using a contraction mapping derived from the first-order conditions. The deterministic dynamic programming problem is used to illustrate the method. Some numerical examples are performed.